Astrometric detection of intermediate-mass black holes at the Galactic Centre. Issue 3 (1st October 2018) - Girma, Eden; Loeb, Abraham
Abstract: We assess the astrometric detectability of intermediate-mass black holes populating the inner parsec of the Milky Way Galaxy. The presence of these objects induces dynamical effects on Sgr A* and the star S2, which could be detected by next generation astrometric instruments that enable microarcsec astrometry. An allowed population of ten 10 4 M⊙ intermediate-mass black holes within one parsec induces an angular shift of${\sim } 65\, μ \rm{as\, yr}^{-1}$ on the position of Sgr A*, corresponding to a perpendicular velocity component magnitude of$1.6\, \rm{km\, s}^{-1}$ . It also induces changes in the orbit of S2 that surpass those induced by general relativity but lie within observational constraints, generating a mean angular shift in periapse and apoapse of 62 and 970 µas, respectively.